2013
DOI: 10.1097/wnr.0b013e32835f66ea
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of cortical and subcortical plasticity following short-term unilateral auditory deprivation in normal hearing adults

Abstract: There is growing evidence that auditory stimulation or deprivation can induce physiological and perceptual changes in the auditory system of normal hearing adults. The present study investigated cortical (hemispheric asymmetry) and subcortical (acoustic reflex threshold) changes in 11 normal hearing adults after 7 days of continuous unilateral earplug use (around 30 dB of attenuation at the high frequencies). The results revealed: (a) a decrease in high frequency acoustic reflex thresholds of around 7 dB in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…The changes in ART are consistent with a change in neural gain occurring at the level of the auditory brainstem. This was confirmed by Maslin et al [2013] who investigated cortical and subcortical activity using functional magnetic resonance imaging and the ART, respectively. After 7 days of unilateral earplug use, the authors found a reduction of 3-7 dB in the ART of the plugged ear but no change in cortical activity.…”
Section: Changes In Neural Gain In Humansmentioning
confidence: 72%
See 3 more Smart Citations
“…The changes in ART are consistent with a change in neural gain occurring at the level of the auditory brainstem. This was confirmed by Maslin et al [2013] who investigated cortical and subcortical activity using functional magnetic resonance imaging and the ART, respectively. After 7 days of unilateral earplug use, the authors found a reduction of 3-7 dB in the ART of the plugged ear but no change in cortical activity.…”
Section: Changes In Neural Gain In Humansmentioning
confidence: 72%
“…Studies have explored the physiological and perceptual effects of temporary augmented stimulation or deprivation in normalhearing listeners [Formby et al, 2003;Maslin et al, 2013;Munro and Blount, 2009;Munro and Merrett, 2013;Munro et al, 2007a, b;Munro et al, 2014]. Formby et al [2003] measured the change in loudness perception using the Contour Test of Loudness Perception, in which subjects were asked to rate the loudness of sounds using 7 loudness categories, ranging from very soft to uncomfortably loud [Cox et al, 1997].…”
Section: Changes In Neural Gain In Humansmentioning
confidence: 99%
See 2 more Smart Citations
“…Subcortical plasticity, on the other hand, has only been studied in human subjects with unilateral earplug induced auditory deprivation (Decker and Howe 1981;Maslin et al 2013;Munro and Blount 2009).…”
Section: Introductionmentioning
confidence: 99%